Pengaruh Luas Ungkapan Sukarela dan Asimetri Informasi Terhadap Cost of Equity Capital pada Perusahaan Publik di Indonesia - Siti AsiaH Murni (The Indonesian Journal of Accounting Research, 2013)
This study examines whether voluntary corporate disclosure level published in annual report and asymmetry information has an effect on cost of equity capital. The purpose of the study is to investigate whether the variances in corporate disclosure level and asymmetry information effect cost of equity capital. The sample consists of 61 companies listed on the Jakarta Stock Exchange in 1999 and 2000. The hypotheses tested was conducted by implementing pooled data method, for period of 1999- 2000. The results  support the hypotheses that voluntary corporate disclosure, information asymmetry and beta have effect on cost of equity capital.  More specifically, the results show that size significantly moderates the relationship between information asymmetry and cost of equity capital, but size does not significantly moderate the relationship between voluntary corporate disclosure level and cost of equity capital.